Douching practices among women in the Bolgatanga municipality of the upper east region of Ghana - Florence Assibi Ziba; Vida Nyagre Yakong; Rockson Asaan Asore; Keville Frederickson; Michele Flynch (BMC, 2019)
Abstract Background Vaginal douching is a common practice among women all over the world. Women douche for various reasons, despite evidence indicating the harmful health effects of the practice. There is lack of data on the practice in Ghana but health behaviors like vaginal douching may be influenced by differences in culture and geography. Therefore, this study sought to assess prevalence and predictors of vaginal douching practices among women of the Bolgatanga Municipality of Ghana. Methods This cross-sectional study was conducted among 200 women from January to March 2016. Results Sixty-seven percent of the women practiced vaginal douching, from which a similar proportion did it daily. Over two-thirds (67.7%) of the women used water for douching. The reasons for douching were cleansing the vagina (67.7%), therapeutic effects (12.8%) and tightening of the vaginal muscles (19.5%). The majority (87.2%) of women who douched were unaware of the harmful health effects associated with the practice. The educational level of the women (p = 0.025) and having knowledge of the dangers associated with douching (p <  0.001) were then significantly associated with douching practices. Conclusion Vaginal douching is commonly practiced by women in the Bolgatanga Municipality. Most of these women douche because they did not know that there are health problems associated with the practice. Health education on the issues of women health is very vital for the improvement of women's health.